Therapeutic Window of Clopidogrel and Ticagrelor in Patients With Critical Limb-Threatening Ischemia. (March 2020) - Dhillon, Ashwat S.; Caro, Jorge; Tun, Han; Armstrong, David G.; Rowe, Vincent; Shavelle, David M.; Clavijo, Leonardo C.
Background: Critical limb-threatening ischemia (CLTI) is associated with an increased risk of major adverse limb events and mortality. High on-treatment platelet reactivity (HPR) is associated with an increased risk of ischemic events, while low on-treatment platelet reactivity (LPR) is associated with an increased risk of bleeding. This study investigates the frequency with which patients with CLTI on clopidogrel or ticagrelor achieve a "therapeutic window" (TW) of platelet inhibition. Methods: Data from the "Switch To Ticagrelor in Critical Limb Ischemia Anti-Platelet Study" were assessed retrospectively to determine the incidence of TW of on-treatment platelet reactivity in 50 consecutive patients with CLTI (mean age: 65.2 ± 10.5 years, 54% male). The data included 4 measurements of patients' platelet reactivity using the VerifyNow P2Y12 Assay: baseline and steady state platelet reactivity on clopidogrel 75 mg daily and on ticagrelor 90 mg twice daily. Results: At baseline, 46% of patients on clopidogrel were within TW of on-treatment platelet reactivity compared to 10% of patients on ticagrelor ( P < .0001). At steady state, 42% of patients on clopidogrel were within the TW compared to 10% of patients on ticagrelor ( P < .0001). Patients on ticagrelor exhibited higher rates of LPR compared to those on clopidogrel at baseline as well as at steady state (baseline 88% vs 18%, steady state 88% vs 28%; P < .0001). Conclusion: Although ticagrelor has been proposed as an alternative for patients with HPR on clopidogrel, the current study observes an excess of platelet inhibition with ticagrelor in most patients with CLTI at a dose of 90 mg twice daily.